The Role of Context in Social Understanding of Autistic Characters: Pragmatic Analysis of the Film “Please Stand By” - Dewi, Laila Nur Fitria; Ahmadi, Annas (Wacana : Jurnal Bahasa, Seni, dan Pengajaran, 2025)
This study examines how contextual factors influence the social skills of Wendy, an autistic protagonist in the film Please Stand By. Adopting a descriptive qualitative design and pragmatic analysis grounded in Wilson and Sperber’s Relevance Theory, the research investigates Wendy’s processing of social cues across everyday conversations and unfamiliar environments during travel. Data comprised dialogue transcripts and observations of nonverbal behaviors, analyzed to identify pragmatic barriers: dependence on concrete rules, difficulty inferring implicit meanings, literal interpretation of unexpected changes, and vulnerability to social manipulation. Findings indicate Wendy’s reliance on explicit, structured instructions to navigate social contexts; when cues were ambiguous or implied, she exhibited misunderstandings and heightened emotional responses. Conversely, detailed guidance enabled accurate adaptation in certain scenarios, highlighting the efficacy of targeted communicative interventions. This study enhances understanding of autism by elucidating context-driven communicative challenges and endorses inclusive strategies to foster social participation among individuals with ASD. Ultimately, the research raises awareness of autism’s social dimensions and offers practical insights for practitioners and society.